Social Media-Based Behavior To Promote Tourist Destination - Noor, Any; Suryana, Marceilla; Amalia, Sholihati (Opción, 2019)
Purpose – Theaims of this study is to investigate social media-based behavior and its potential to promote tourist destination among Indonesian tourism university students. Design/methodology approach – The methodology used in this study were quantitative and qualitative approaches as a complementary way. Data were collected from a total of 321 tourism university students. Findings – The research finding strongly support tourism student behavior as consistent with previous lit- erature with some behavior that tourism student is high dependent on social media with low ability in making blog, vlog and forum. Another important finding, so- cial media lead to the opportunities of Indonesia tourism university student doing business in tourism field. Originality/value – The original contribution is that this study not only provide valuable information about young consumer behavior in using social media, but also enriches the existing literature, specially concentrating on Indonesian behavioral background. To the best of author knowledge, this study is the first study specifically focusing in Indonesian tourism university student be- havior in promoting tourist destination through the social media.